Assessing the potential of local beneficial halophytes in desalination - Sanleri, Kwabena Azure (University of Cape Coast, 2024)
Cape Coast, part of Ghana's coastal region, has a rich diversity of plant species with various potential uses. These plant species, called halophytes, possess qualities that enable them to grow and thrive in saline environments. This research aimed to identify and explore these plants' nutritional, ecological, and medicinal significance, examining their salt tolerance and desalination abilities. The halophytes were identified using an image recognition method, where images of the plants were keyed into Pl@ntNet Identify website (https://identify.plantnet.org/), an online software for plant identification. Five halophytes, namely, Ipomoea aquatica, Lactuca taraxacifolia, Paspalum vaginatum, Sesuvium portulacastrum and Talinum triangulare, were selected from the identified halophytes for a greenhouse experiment using a Completely Randomized Design (CRD) to assess their response to varying salt concentrations (0, 25 and 50 dS/m) and soil types (sea sand and arable soil). Results revealed significant growth and salt tolerance variations among the studied halophytes, with P. vaginatum and S. portulacastrum demonstrating remarkable phytoremediation capabilities. These plants exhibited the ability to mitigate soil salinity and reduce the accumulation of toxic ions in soils, highlighting their potential for addressing soil and water salinity issues in affected environments. Another greenhouse experiment was conducted to assess the desalination abilities of S. portulacastrum (the most promising halophyte from the initial experiment) to desalinate saline water in a hydroponic system on a vertical farming structure. The factors for this experiment were the salt concentrations (0, 25 and 50 dS/m) and planting distances (15, 20, 30 and 40 cm). Sesuvium portulacastrum exhibited limited desalination capacity in reducing the EC and TDS of the saline water. However, it contributed to a reduction in the pH of the saline water. Further research is necessary to discover this pH-reducing effect's underlying mechanisms and potential applications in water treatment processes. Overall, this study underscores the significance of harnessing the ethnobotanical resources in Ghana for sustainable development and environmental conservation.
xv,179p:, ill.